2007
DOI: 10.1111/j.1365-2664.2007.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing dispersal and corridor models using landscape genetics

Abstract: Summary 1.Better tools are needed to predict population connectivity in complex landscapes. 'Least-cost modelling' is one commonly employed approach in which dispersal costs are assigned to distinct habitat types and the least-costly dispersal paths among habitat patches are calculated using a geographical information system (GIS). Because adequate data on dispersal are usually lacking, dispersal costs are often assigned solely from expert opinion. Spatially explicit, high-resolution genetic data may be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
253
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(259 citation statements)
references
References 35 publications
5
253
0
1
Order By: Relevance
“…Landscape genetic analyses using LCP models assume that genetic distances between population pairs increase with cost-weighted distances measured along the optimal (leastcost) routes connecting them (9,(13)(14)(15)(16). We calculated LCP distances (reflecting the shortest within-habitat routes connecting sample pairs; Figs.…”
Section: Ibd Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landscape genetic analyses using LCP models assume that genetic distances between population pairs increase with cost-weighted distances measured along the optimal (leastcost) routes connecting them (9,(13)(14)(15)(16). We calculated LCP distances (reflecting the shortest within-habitat routes connecting sample pairs; Figs.…”
Section: Ibd Predictionsmentioning
confidence: 99%
“…This hinders hypothesis testing and leaves conservation planners without validated metrics of how landscape change will affect genetic connectivity. Although a growing number of studies are incorporating landscape data into genetic predictions and conservation plans using least-cost path (LCP) modeling (9,(13)(14)(15)(16), gene flow among real populations is not restricted to single, optimal pathways, as LCP models assume; rather, it occurs over multiple pathways and often involves indirect allele movements spanning many generations (17). Thus, to support conservation planning and to enable hypothesis testing in landscape genetics, theoretically justified models of how landscape features facilitate or impede gene flow over multiple, direct and indirect pathways are needed.…”
mentioning
confidence: 99%
“…The approach has been widely applied in conservation biology and landscape ecology as a means to identify paths that support gene flow between populations of organisms that require high-quality habitat linkages (Macdonald & Johnson 2001). Indeed, a common outcome of these studies is that distances defined by functional environmental models better explain observed dispersal, population dynamics or genetic differentiation than Euclidean distance, reinforcing the need for improved geographical measures of ecological connectivity to predict rates and likelihoods of spread (Michels et al 2001;Adriaensen et al 2003;Stevens et al 2006;Epps et al 2007).…”
Section: Functional Environmental Modelsmentioning
confidence: 99%
“…Opportunities for dispersal may exist in southern Africa because protected areas are within close proximity of each other and are embedded in a matrix of mostly untransformed habitats with few people (Cushman et al 2010;Mittermeier et al 2003). Furthermore, elephants are ideal candidates for designing corridors because they are an umbrella species, often co-occurring with other species of conservation concern (Epps et al 2007). In this paper, we will assess the potential for connectivity between existing elephant populations in southern Africa using circuit theory and resource selection function (RSF) models.…”
Section: Introductionmentioning
confidence: 99%